Image_1_Metagenomic analysis of gut microbiota and antibiotic-resistant genes in Anser erythropus wintering at Shengjin and Caizi Lakes in China.pdf - Gang Liu (81776); Na Xu (188237); Jiahui Feng (11458587) (2023)
Migratory birds are the primary source and reservoir of antibiotic-resistant genes (ARGs) related to their gut microbes. In this study, we performed metagenomics analysis to study the gut microbial communities and ARGs of Anser erythropus wintering at Shengjin (SJ) and Caizi (CZ) Lakes. The results showed that bacteria, fungi, viruses, and archaea were the dominant gut microbes. Principal component analysis (PCA) indicated that the microbiota compositions significantly differed between the two populations. Diet may be the most crucial driver of the gut microbial communities for A. erythropus. This species fed exclusively on Poaceae spp. at Shengjin Lake and primarily on Carex spp. at Caizi Lake. Tetracycline, macrolide, fluoroquinolone, phenicol, and peptide antibiotics were the dominant resistant types. ARGs had a significantly higher abundance of operational taxonomic units (OTUs) in the Shengjin Lake samples than in Caizi Lake samples. PCA indicated that most Shengjin Lake samples significantly differed in gut microbiota composition from those obtained at Caizi Lake. This difference in gut microbiota composition between the two lakes' samples is attributed to more extensive aquaculture operations and poultry farms surrounding Shengjin Lake than Caizi Lake. ARGs–microbes associations indicated that 24 bacterial species, commonly used as indicators of antibiotic resistance in surveillance efforts, were abundant in wintering A. erythropus. The results revealed the composition and structural characteristics of the gut microbiota and ARGs of A. erythropus, pointing to their high sensitivities to diet habits at both lakes. This study also provides primary data for risk prevention and control of potential harmful pathogens that could endanger public health and therefore are of major significance to epidemiological and public health.